Complexity and Conservation of Thermospermine-Responsive uORFs of SAC51 Family Genes in Angiosperms - Ishitsuka, Soichi; Yamamoto, Mai; Miyamoto, Minaho; Kuwashiro, Yoshitaka; Imai, Akihiro; Motose, Hiroyasu; Takahashi, Taku (Frontiers in Plant Science, 2019)
ACAULIS5 (ACL5) encodes thermospermine synthase in Arabidopsis and its loss-of-function mutant acl5 shows excess xylem differentiation and severe dwarfism. SAC51 encodes a basic helix-loop-helix (bHLH) protein and was identified from sac51-d, a dominant suppressor mutant of acl5, which restores the wild-type phenotype without thermospermine. The 5’ leader of the SAC51 mRNA contains multiple upstream open-reading frames (uORFs) and sac51-d has a premature stop codon in the 4th uORF. This uORF is conserved among SAC51 family genes in vascular plants. According to the GUS reporter assay, the SAC51 promoter was not responsive to thermospermine but the SAC51 5’ leader fused to the constitutive 35S promoter enhanced the GUS activity in response to thermospermine. Disruption experiments of each start codon of the SAC51 uORFs revealed that uORF4 and uORF6 whose start codon corresponds to the second methionine codon of uORF4 had an inhibitory effect on the main ORF translation while the other four uORFs rather had a stimulatory effect. The response of the 5’ leader to thermospermine was retained after disruption of each one of six start codons of these uORFs but abolished by mutating both uORF4 and uORF6 start codons, suggesting the importance of the C-terminal sequence shared by these uORFs in the action of thermospermine. We introduced GUS fusions with 5’ leaders of SAC51 family genes from other angiosperm species into Arabidopsis and found that all 5’ leaders responsive to thermospermine, so far examined, contained these two conserved and overlapping uORFs.